Vector bundles over three-dimensional spherical space forms - Esdras Teixeira Costa; Oziride Manzoli Neto; Mauro Spreafico (International Journal of Mathematics and Mathematical Sciences)
We consider the problem of enumerating the G-bundles over low-dimensional manifolds (dimension ≤3) and in particular vector bundles over the three-dimensional spherical space forms. We give a complete answer to these questions and we give tables for the possible vector bundles over the 3-dimensional spherical space forms.